PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP KEMAMPUAN MENGIDENTIFIKASI HEWAN PADA PESERTA DIDIK KELAS V MIS AL-KHAIRAAT TADA KECAMATAN TINOMBO SELATAN - Maragau, Rusdaniati H; Arda, Arda; Adawiyah, Siti Rabiatul (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2023)
The background of this research is the condition of students at MIS Al-Khairaat Tada who did not understand the science learning material. The learning carried out is conventional and not student-centered. This research starts from the problem of whether there is an effect of implementing the STAD type cooperative learning model on the ability to identify animals in class V students at MIS Al-Khairaat Tada? The sample for this research was 13 class V students of MIS Al-Khairaat Tada. This study uses a quantitative approach. Data collection techniques through tests, observation and documentation. The data analysis techniques used are normality test, regression test and hypothesis test. Hypothesis testing using the t test obtained a significance value of 0,000. This value is smaller than 0,05 so Ha is accepted and H0 is rejected. These results indicate that there is an influence of the application of the STAD type cooperative learning model on the ability to identify animals in class V students at MIS Al-Khairaat Tada.